A multi-Fc-species system for recombinant antibody production - Moutel, Sandrine (BioMed Central, 2009)
BACKGROUND: Genomic, transcriptomic and proteomic projects often suffer from a lack of functional validation creating a strong demand for specific and versatile antibodies. Antibody phage display represents an attractive approach to select rapidly in vitro the equivalent of monoclonal antibodies, like single chain Fv antibodies, in an inexpensive and animal free way. However, so far, recombinant antibodies have not managed to impose themselves as efficient alternatives to natural antibodies. RESULTS: We developed a series of vectors that allow one to easily fuse single chain Fv antibodies to Fc domains of immunoglobulins, improving their sensitivity and facilitating their use. This series enables the fusion of single chain Fv antibodies with human, mouse or rabbit Fc so that a given antibody is no longer restricted to a particular species. This opens up unlimited multiplexing possibilities and gives additional value to recombinant antibodies. We also show that this multi-Fc species production system can be applied to natural monoclonal antibodies cloned as single chain Fv antibodies and we converted the widely used 9E10 mouse anti-Myc-tag antibody into a human and a rabbit antibody. CONCLUSION: Altogether, this new expression system, that brings constant quality, sensitivity and unique versatility, will be important to broaden the use of recombinant and natural monoclonal antibodies both for laboratory and diagnosis use.